Gender education in the practice of women's agricultural laborers in Enrekang Regency - Sabar, Wardihan; Rahim, Abdul; Hastuti, Diah Retno Dwi (Universitas Negeri Yogyakarta, 2022)
This study aims to determine the implementation of gender education values in the socio-economic life of female farmers in Enrekang Regency. The values of gender education in this study are viewed from the aspect of knowledge about gender, practices related to the importance, and gender relations to improve the level of the economic welfare of women farmers. This study uses a case study approach, involving 8 informants who were selected using a purposive technique. Data was collected by using documentation techniques and deepening with instruments in the form of interview guides. The results of this study indicate that in general the term gender is not widely known by female farm workers in this area. They do not know much about the division of roles in Islamic teachings, they only understand that every woman must obey her husband. The division of roles in the home life of women farm workers is well integrated. They have never heard of or received stereotypes, marginalization, or work dichotomy based on sex, nor has there been any pressure from their husbands to join or not work to help the household economy. All are based on economic considerations, and a mutual understanding of household conditions. Homework that is not natural can be done alternately between husband and wife. This study did not find any government programs or activities in the form of empowerment that supports gender mainstreaming or gender education so it became one of the important points in the research.Pendidikan Gender dan Praktiknya pada wanita petani di EnrekangPenelitian bertujuan untuk mengetahui implementasi nilai-nilai pendidikan gender dalam kehidupan sosial ekonomi petani perempuan di Kabupaten Enrekang. Penelitian ini menggunakan pendekatan studi kasus, dengan melibatkan 8 informan yang dipilih dengan menggunakan teknik purposive. Pengumpulan data dilakukan dengan teknik dokumentasi dan pendalaman dengan instrumen berupa pedoman wawancara. Hasil penelitian ini menunjukkan bahwa secara umum istilah gender tidak banyak dikenal oleh perempuan buruh tani. Mereka tidak tahu banyak tentang pembagian peran dalam ajaran Islam, mereka hanya mengerti bahwa setiap wanita harus taat pada suaminya. Pembagian peran dalam kehidupan rumah tangga perempuan buruh tani terintegrasi dengan baik. Mereka tidak pernah mendengar atau menerima stereotip, marginalisasi, atau dikotomi pekerjaan berdasarkan jenis kelamin, juga tidak pernah ada tekanan dari suami untuk ikut atau tidak bekerja membantu perekonomian rumah tangga. Semua didasarkan pada pertimbangan ekonomi, dan pemahaman bersama tentang kondisi rumah tangga. Pekerjaan rumah yang tidak wajar bisa dilakukan secara bergantian antara suami dan istri. Kajian ini tidak menemukan adanya program atau kegiatan pemerintah berupa pemberdayaan yang mendukung pengarusutamaan gender atau pendidikan gender sehingga menjadi salah satu poin penting dalam penelitian ini.